2020
DOI: 10.1016/j.ccell.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging Detects Resistance to PI3Kα Inhibition Mediated by Persistent FOXM1 Expression in ER+ Breast Cancer

Abstract: Summary PIK3CA , encoding the PI3Kα isoform, is the most frequently mutated oncogene in estrogen receptor (ER)-positive breast cancer. Isoform-selective PI3K inhibitors are used clinically but intrinsic and acquired resistance limits their utility. Improved selection of patients that will benefit from these drugs requires predictive biomarkers. We show here that persistent FOXM1 expression following drug treatment is a biomarker of resistance to PI3Kα inhibition in ER + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 76 publications
(120 reference statements)
0
45
0
Order By: Relevance
“…2020 ), as had been done previously in established cell line xenograft models of glioblastoma ( Venkatesh et al., 2012 ) and breast cancer ( Ward, Venkatesh et al. 2010 , Ros et al. 2020 ).…”
Section: Before You Beginmentioning
confidence: 95%
See 2 more Smart Citations
“…2020 ), as had been done previously in established cell line xenograft models of glioblastoma ( Venkatesh et al., 2012 ) and breast cancer ( Ward, Venkatesh et al. 2010 , Ros et al. 2020 ).…”
Section: Before You Beginmentioning
confidence: 95%
“…The technique has been used with patient-derived xenograft models of breast cancer, where we used it to detect response to PI3K alpha inhibitors ( Ros et al. 2020 ), as had been done previously in established cell line xenograft models of glioblastoma ( Venkatesh et al., 2012 ) and breast cancer ( Ward, Venkatesh et al.…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation
“…This is occasionally determined by genetic predisposition, whereby the selection of rare pre-existing resistance-conferring genetic mutations limit overall therapy sensitivity. In some of these cases, the development of drug resistance may be mediated by loss of PTEN expression; altered expression of RSK3/4, PIM, AXL, FOXM1, NOTCH, c-MYC, PDK-1-SGK1, SGK3 and CDK4/6; or KRAS mutations [ 77 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. However, under certain contexts downregulation of the targeted pathways can result in genetically independent intrinsic compensatory mechanisms with survival rather than continued proliferation being the ultimate outcome.…”
Section: Reactivation Of Pi3k Signallingmentioning
confidence: 99%
“…This effect is possibly due to increased IR expression within the tumours, suggesting these results as likely biomarkers associated with patient responses following treatment [ 151 ]. It has also recently been reported that lactate can serve as surrogate to measure glycolytic flux and can effectively determine PI3K pathway inhibition [ 125 , 152 ].…”
Section: Reactivation Of Pi3k Signallingmentioning
confidence: 99%